RECONSTRUCTION OF THE ANNEALED AND GRAY CAST IRON WORKSHOP AT GAG “MZGG” - V. A. Vershinin (Литьë и металлургия, 2005)
The advantages of moulding system DISA 230F (Denmark) are given. It is shown that enterprise gets economic effect from reduction of net cost of 1 tone casting of annealed and gray cast iron.